2016
DOI: 10.1111/hae.13051
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tranexamic acid for the prevention of bleeding in patients with von Willebrand disease and Glanzmann thrombasthenia: a controlled, before and after trial

Abstract: The results suggest that TXA is safe and effective to reduce bleeding and use of factor concentrates in VWD patients. In addition, TXA therapy can decrease bleeding in GT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…We conducted 3 systematic reviews of case series, 1 for each of the intervention arms. We included 21 case series: 8 in which patients underwent a desmopressin trial and were treated based on results, [60][61][62][63][64][65][66][67] 9 in which patients did not undergo a desmopressin trial and were treated with VWF concentrate or tranexamic acid, 26,38,45,[68][69][70][71][72][73] and 4 in which patients did not undergo a desmopressin trial but were treated with desmopressin empirically. [74][75][76][77] The EtD framework for this recommendation is available online at https://guidelines.ash.gradepro.org/profile/fnGuafOe504.…”
Section: Recommendation 2bmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted 3 systematic reviews of case series, 1 for each of the intervention arms. We included 21 case series: 8 in which patients underwent a desmopressin trial and were treated based on results, [60][61][62][63][64][65][66][67] 9 in which patients did not undergo a desmopressin trial and were treated with VWF concentrate or tranexamic acid, 26,38,45,[68][69][70][71][72][73] and 4 in which patients did not undergo a desmopressin trial but were treated with desmopressin empirically. [74][75][76][77] The EtD framework for this recommendation is available online at https://guidelines.ash.gradepro.org/profile/fnGuafOe504.…”
Section: Recommendation 2bmentioning
confidence: 99%
“…38,45,69 When used for long-term prophylaxis, the strategy of using tranexamic acid only reduced annual oropharyngeal bleeding episodes from 30 to 16. 68 For the strategy of empiric treatment with desmopressin for surgical prophylaxis without the results of a desmopressin trial, 1 study reported that hemostasis was excellent in 93% of patients with mild type 1 VWD and 73% in patients with moderate type 1 VWD, with a mean hospitalization length of 6.3 days. 76 This strategy, when used to manage acute bleeding episodes, was judged to have excellent efficacy in 83% and good efficacy in 14% of 254 bleeding episodes in patients with mild type 1 VWD.…”
Section: Recommendation 2bmentioning
confidence: 99%
“…In the case of a propensity towards major bleeding after severe trauma, tranexamic acid (1 g iv over 10 min) should be administered as soon as possible, followed by 1 g iv over 8 h [121,122]. For VWD patients with thrombocytopenia, antifibrinolytic therapy may be administered as an adjuvant treatment in cases of oral mucosal bleeding or excessive menstrual bleeding [123,124].…”
Section: Recommendation 17: Antifibrinolytic Therapy Is Required Whenmentioning
confidence: 99%
“…22 They have also been administered to people with a variety of hemostatic disorders, including VWD and Glanzmann thrombasthenia, with a clinical assessment of decreased numbers of bleeding episodes when administered prophylactically. 23 Aminocaproic acid was administered to the dog of this report, as drug-related adverse effects are rare 24 , although its efficacy in managing hemorrhage due to intrinsic platelet dysfunction has not been investigated in veterinary medicine. The dog was also treated with fresh whole blood and PRP transfusions shortly after identification of the hemoperitoneum, given the probability of a platelet P2Y12 defect based on the breed.…”
Section: Discussionmentioning
confidence: 99%